Resveratrol overcomes TRAIL resistance in human colon cancer cells (Bangladesh Journal of Pharmacology, 2015)
Resveratrol is a stilbenoid compound, and a promising potent chemopreventive bioactive agent. Here, we showed for the first time that the combined treatment with resveratrol and TRAIL drastically induced apoptosis in human colon cancer cells when compared to single treatments. Further, resveratrol markedly up-regulated TRAIL receptors, DR5 and DR4 and the results revealed that DR5 siRNA efficiently blocked apoptosis induced by the co-treatment with resveratrol and TRAIL, indicating that DR5 up-regulation by resveratrol helps to enhance TRAIL actions. In addition, the combined effect was tested on normal human cells. All the obtained results suggested that resveratrol is very useful for TRAIL-based treatments for cancer.